Discrimination of sexual minorities in emerging markets: Can the needle be moved? - Cevat Giray Aksoy; Christopher Carpenter; Ralph De Haas; Mathias Dolls; Lisa Windsteiger (EconPol Forum, 2023)
Providing information about the economic cost of sexual orientation discrimination significantly increases support for measures to safeguard equal employment opportuni ties for lesbians and gays. Treatment effect spills over to support for equal employment opportunities based on ethnic origin, religious beliefs, nationality, gender, and disability, but not to LGB support in other aspects of life. Informing people that according to the WHO homosexuality is not a mental disease does not cause more support for equal employment opportunities, but does result in improved attitudes about sexual minorities in non-economic aspects of life. Effects are concentrated among those individuals who trust the WHO. Political actors wanting to achieve the policy goal of expanding non-discrimination employment protections should consider information campaigns that stress the costs of discrimination as opposed to trying to change more fundamental views about homosexuality
Keywords: 330